THE CORRELATION BETWEEN STUDENTS’ METACOGNITION AND THEIR ACADEMIC ACHIEVEMENT IN ENGLISH SUBJECT AT SMAN 8 KENDARI - Amrin, Amrin; Tanduklangi, Amri; Mursalim, Mursalim (Journal of Teaching of English, 2019)
The study aimed at investigating the correlation between students’ metacognition and their academic achievement at the eleventh grade of SMAN 8 Kendari. The objective of the study is to answer the following research question: is there any significant correlation between student’s metacognition and their academic achievement in English subject at SMAN 8 Kendari?. The study was correlation research study, which employed quantitative research methods.  The  data  was  collected  from  46  participants who are from SMA N 8 Kendari class XI IPA I and IPS II. The data collection was carried out by using a Metacognition questionnaire and English achievement students   from   report   card.   Researcher   used   cluster random  sampling  technique  in  taking  the  sample.  The data of the study was analyzed through Spearman correlation analysis of SPSS 16. The result shows that the coefficient correlation that obtained from the computation is  0,443  and  categorized  as  moderate  correlation.  The result   shows   that   there   is   a   significant   correlation between students’ metacognition and their academic achievement in English subject. This conclusion of this study  was  drawn  through  the  result  of computation which showed that the value of coefficient correlation (r) between two variables, that was students’ metacognition as  the  variable  X  and  academic  achievement  as  the variable Y, is as moderate as that of the Spearman correlation table with 0,05 level significant. Further, the data showed that there was a moderate correlation. Therefore,  it  means that  the  alternative  hypothesis was accepted    and    the    null    hypothesis    was    rejected. Keywords: Metacognition, Academic Achievement